Integrative analysis and identification of key elements and pathways regulated by Traditional Chinese Medicine (Yiqi Sanjie formula) in colorectal cancer - Wan, Xianghui; Tou, Fangfang; Zeng, Jiquan; Chen, Xinyi; Li, Shanshan; Chen, Lanyu; Zheng, Zhi; Rao, Jun (Frontiers in Pharmacology, 2022)
The clinical efficacy of Yiqi Sanjie (YQSJ) formula in the treatment of stage III colorectal cancer (CRC) has been demonstrated. However, the underlying antitumor mechanisms remain poorly understood. The aim of the present study was to comprehensively characterize the molecular and microbiota changes in colon tissues and fecal samples from CRC mice and in CRC cell lines treated with YQSJ or its main active component, peiminine. Integrative tandem mass tag-based proteomics and ultra-performance liquid chromatography coupled with time-of-flight tandem mass spectrometry metabolomics were used to analyze azoxymethane/dextran sulfate sodium-induced CRC mouse colon tissues. The results showed that 0.8% (57/7568) of all detected tissue proteins and 3.2% (37/1141) of all detected tissue metabolites were significantly changed by YQSJ treatment, with enrichment in ten and six pathways associated with colon proteins and metabolites, respectively. The enriched pathways were related to inflammation, sphingolipid metabolism, and cholesterol metabolism. Metabolomics analysis of fecal samples from YQSJ-treated mice identified 121 altered fecal metabolites and seven enriched pathways including protein digestion and absorption pathway. 16S rRNA sequencing analysis of fecal samples indicated that YQSJ restored the CRC mouse microbiota structure by increasing the levels of beneficial bacteria such as Ruminococcus_1 and Prevotellaceae_UCG_001. In HCT-116 cells treated with peiminine, data-independent acquisition-based proteomics analysis showed that 1073 of the 7152 identified proteins were significantly altered and involved in 33 pathways including DNA damage repair, ferroptosis, and TGF-β signaling. The present study identified key regulatory elements (proteins/metabolites/bacteria) and pathways involved in the antitumor mechanisms of YQSJ, suggesting new potential therapeutic targets in CRC.